2013
DOI: 10.1177/0960327112468177
|View full text |Cite
|
Sign up to set email alerts
|

Function of the liver and bile ducts in humans exposed to lead

Abstract: Lead is very common in the environment, and it is therefore important to characterize its possible adverse health effects. The aim of this study was to evaluate the impact of lead exposure on selected functions of the liver and bile ducts in people who are chronically exposed to the metal because of their occupations. To provide this information, the activity of specific enzymes and the bilirubin concentration were determined in blood serum, and morphological parameters of the liver and bile ducts were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Moreover, human exposure to Pb compounds has been seen to cause liver enlargement and to activate inflammatory reactions characterized by moderate cholestasis within the bile ducts; these conditions are more evident in subjects with higher Pb exposure levels [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, human exposure to Pb compounds has been seen to cause liver enlargement and to activate inflammatory reactions characterized by moderate cholestasis within the bile ducts; these conditions are more evident in subjects with higher Pb exposure levels [8]. …”
Section: Introductionmentioning
confidence: 99%
“…ALT (P < 0.00, r = 0.707) and AST (P < 0.00, r = 0.776) levels during three years of follow-up in the exposed lead mineworkers significantly increased as compared with the non-exposure workers, which illustrates the occurrence of hepatocellular injury. Previous studies have suggested that elevated serum AST and ALK levels may be due to mitochondrial degradation after the destruction of liver cells [35] , [36] .…”
Section: Discussionmentioning
confidence: 99%
“…ALT (r: 0.977, p < 0.001) and AST (r: 0.869, p < 0.001) levels during three years of follow-up in the exposed leadmine workers signi cantly increased as compared with the non-exposure subjects, which illustrates the occurrence of hepatocellular injury. Previous studies have suggested that elevated serum AST and ALK levels may be due to mitochondrial degradation after the destruction of liver cells [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%